STUDI DESKRIPTIF: PERILAKU DIGITAL PARENTING TENTANG PENGGUNAAN GADGET PADA ANAK USIA SEKOLAH - Lestari, Puji; Saparwati, Mona; Aniroh, Umi (Coping: Community of Publishing in Nursing; Vol 11 No 5 (2023): Oktober 2023DO - 10.24843/coping.2023.v11.i05.p13, 2023)
The presence of the development of gadgets has a positive impact on children, including providing ease in communicating, digging for information to entertainment, but in various situations the presence of technological developments actually has a negative impact on children, one of which is dependence or addiction. Children who are addicted become more emotional, form a rebellious character because of the desire not to be disturbed when playing gadgets, become lazy, and lazy to learn. Parents have an obligation to control and in addition supervise every form of information received by children through gadgets. This study aims to determine the picture of digital parenting behavior about the use of gadgets in school-age children in Semarang City. This research is a descriptive research with a cross sectional approach. The data is presented descriptively to describe the frequency distribution of digital parenting behavior about gadget use in elementary school-age children in Semarang City.  The results showed that digital parenting behavior in most categories was sufficient (68,0%). It is expected that parents will further increase digital parenting behavior about the use of gadgets to prevent and control the occurrence of gadget addiction in school-age children.